A Review of the Biology, Ecology, and Management of Plum Curculio (Coleoptera: Curculionidae). (10th November 2020) - Lampasona, Timothy P; Rodriguez-Saona, Cesar; Leskey, Tracy C; Nielsen, Anne L
Abstract: The plum curculio, Conotrachelus nenuphar Herbst (Coleoptera: Curculionidae), is an insect native to the Americas that is a serious pest of stone and pome fruits in the United States and Canada. Failure to effectively manage this insect may result in up to 85% damaged fruit at harvest, as well as early season fruit abortion. Conotrachelus nenuphar is oligophagous, feeding and ovipositing on many Rosaceous plants, including apple, peach, plum, cherry, quince, and pear. Additionally, C. nenuphar in limited geographic ranges utilizes alternate hosts such as highbush blueberry (Ericaceae) and Muscadine grape (Vitaceae). Despite its long history as a pest, integrated pest management (IPM) lags behind similarly damaging native fruit pests. Although significant progress has been made on the identification of attractive lures for monitoring C. nenuphar adults, development of behaviorally based management strategies, and biological control with entomopathogenic nematodes, growers continue to rely heavily on top-down chemical inputs to manage this pest. Most of the research to date comes from studies done in apples where alternative management practices for C. nenuphar have, to some extent, been adopted; however, less IPM-based information is available for other susceptible crops. In this review, we summarize the history, biology, ecology, behavior, and control of C. nenuphar and future directions for IPM research.